Transforming the European Union's phosphorus governance through holistic and intersectoral framings - Kalpakchiev, Teodor; Fraundorfer, Markus; Jacobs, Brent; Martin-Ortega, Julia; Cordell, Dana (Frontiers in Sustainable Resource Management, 2023)
This review paper presents a critical perspective on the transformation of phosphorus governance in the European Union to support food and environmental security, which are subject to systemic shocks. It presents three major limitations that act as constraints to this process: (1) the predominance of technical studies, which produce isolated meanings that fail to address the socio-political aspect of phosphorus management and cannot be translated into policy foresight; (2) approaches to change dominated by the linear resource efficiency paradigm narrowly confined within sectoral responses to system shocks; and (3) the constrained policy understanding of the circular economy, which hampers system change as phosphorus reuse is seen primarily as part of the biological cycle of the circular economy and does not advance critical perspectives. We argue that the siloed and heavy regulatory load related to phosphorus produces technocratic and incremental policy revisions, singular state-level approaches and reductionist prisms that exclude extraterritoriality. These exacerbate the inability of institutions to translate technical studies into policy foresight and counter the pervasiveness of linearity. Phosphorus requires instead a holistic and intersectoral governance object that is integrated with the multiple transition instruments on the policy-making agenda of the European Union. To achieve phosphorus sustainability and avoid the dependence on shocks for its self-renewal, phosphorus governance needs to overcome the technocratic incrementalism of individual sectors and adapt to alternative discursive framings that transcend the existing compartmentalization of its meanings. This would require disentangling phosphorus as a contested arena of controversial stakeholder priorities and selectively amplifying the discursive framings that can politicize and enhance its ubiquitous importance. While phosphorus has its unique properties, such an approach can be of relevance to other elements.